An Untoward Effect: Anticoagulation Therapy in Cancer Patients Leads to Gastrointestinal Bleeding and Increased Mortality - Mathew, Dr. Arine (International Journal of Innovative Research in Medical Science, 2018)
Cancer, a condition involving uncontrolled division of cells, ranks second among leading causes of death worldwide.[1] According to an estimate, cancer will contribute 609,640 deaths in the year 2018 in United States.[2] Therefore, cancer is a major public concern as it has high morbidity and mortality rates. The patients with cancer are at high risk of developing venous thromboembolism (VTE) as it is a hypercoagulable state.[3] Therefore, thrombotic events are a major cause of morbidity and mortality among the patients with cancer.[4,5] Recommendations of anticoagulation in acute VTE are same in the patients with or without cancer.[3] Anticoagulation prophylaxis and therapy is recommended in the patients with cancer who are hospitalized with acute illness or undergoing major surgery and those who have developed VTE, respectively.[6] Usually, low molecular weight heparin (LMWH), vitamin K antagonist (VKA) and direct oral anticoagulants are used for the treatment of VTE in the patients with cancer. The purpose of this anticoagulation is to prevent extension, recurrence and embolism of thrombus. However, higher recurrence of VTE and risk of bleeding complicates the treatment.